1989
DOI: 10.1590/s0101-81751989000300014
|View full text |Cite
|
Sign up to set email alerts
|

Philornis Meinert, 1890: key to adults (Diptera, Muscidae, Reinwardtinae)

Abstract: A key to adults of40 of the 49 knOlrn species ofPhilornis is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
0
1
0
2
Order By: Relevance
“…A las moscas adultas se les colocó una etiqueta con la especie de colibrí hospedero. Para la identificación de las especies de mosca se utilizaron las guías de Carvalho et al 2005, Couri (1984Couri ( , 1989 y Pont (1972).…”
Section: Materiales Y Métodosunclassified
“…A las moscas adultas se les colocó una etiqueta con la especie de colibrí hospedero. Para la identificación de las especies de mosca se utilizaron las guías de Carvalho et al 2005, Couri (1984Couri ( , 1989 y Pont (1972).…”
Section: Materiales Y Métodosunclassified
“…Some authors (Arendt, 1985;Couri, 1999) suggested that eggs or already-hatched larvae are laid in nest material and larvae then seek for their hosts. So far, oviparity was observed only for the free living coprophagous larvae of Philornis rufoscutellaris (Couri, 1983) and for two species with free living semi-hematophagous larvae: Philornis downsi (Dodge and Aitken, 1968) (Lincango and Causton, 2008) and Philornis falsificus (Dodge and Aitken, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…The larvae of flies in the genus Philornis interact with bird populations throughout the tropical and subtropical regions of the Americas as scavengers of fecal matter (coprophages) or parasites that consume fluids and tissue from their host (hematophages) (Aiken 1913, Nielsen 1913, Aldrich 1923, Dodge 1955, Héctor 1982, Couri 1985, Uhazy and Arendt 1986, Young 1993). Within the hematophages, both subcutaneous and free-living larvae can occur (Dodge 1963, Couri 1999.…”
mentioning
confidence: 99%